2014
DOI: 10.1088/1758-5082/6/3/035013
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic fabrication of a three-level hierarchical calcium phosphate/collagen/hydroxyapatite scaffold for bone tissue engineering

Abstract: A three-level hierarchical calcium phosphate/collagen/hydroxyapatite (CaP/Col/HAp) scaffold for bone tissue engineering was developed using biomimetic synthesis. Porous CaP ceramics were first prepared as substrate materials to mimic the porous bone structure. A second-level Col network was then composited into porous CaP ceramics by vacuum infusion. Finally, a third-level HAp layer was achieved by biomimetic mineralization. The three-level hierarchical biomimetic scaffold was characterized using scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…Therefore, to solve the aforementioned problems, researchers are devoting more attention to the biomimetic mineralization of collagen scaffolds. 12,16,17,[21][22][23] The aforementioned works primarily focus on depositing HA crystals outside the collagen fibrils using traditional mineralization methods, such as immersing the collagen scaffolds in different modified simulated body fluids (SBFs). This process is called extrafibrillar mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to solve the aforementioned problems, researchers are devoting more attention to the biomimetic mineralization of collagen scaffolds. 12,16,17,[21][22][23] The aforementioned works primarily focus on depositing HA crystals outside the collagen fibrils using traditional mineralization methods, such as immersing the collagen scaffolds in different modified simulated body fluids (SBFs). This process is called extrafibrillar mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Research on a novel chitosan microsphere/scaffold system by double crosslinkers 6) . Porous HA scaffolds dimensions were sectioned into 3×3×5 mm blocks.…”
Section: Preparation Of Materialsmentioning
confidence: 99%
“…Large quantities of bone grafting materials that contain hydroxyapatite (HA) as the main natural bone mineral [1][2][3] have been studied. Alzubaydi et al [4][5][6] reported that HA scaffold can adsorb cells and thus control the release of protein drugs for application in bone tissue engineering. The bone ingrowth from the surrounding bone tissue into the porous scaffold results in biological anchoring.…”
Section: Introductionmentioning
confidence: 99%
“…Similarities between calcium phosphate (CaP) and the mineral content in bone tissue were the reason why calcium phosphate was chosen for this study [3].Calcium phosphate (CaP) has been used for repairing bone defects, dental and bone tissue applications in the human body since 1920 [4].Calcium phosphate (CaP) is a type of ceramic material that is biocompatible, non-toxic and resorbable. Furthermore, calcium phosphate (CaP) is a bioactive and osteoconductive material that can promote new bone growth and promote cellular function and expression [3,5] . The lack of the calcium phosphate (CaP) makes it limited in the application of artificial bone implant [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, calcium phosphate (CaP) is a bioactive and osteoconductive material that can promote new bone growth and promote cellular function and expression [3,5] . The lack of the calcium phosphate (CaP) makes it limited in the application of artificial bone implant [3,5,6]. Due to that, the combination of different materials known as composite material have been introduced to improve the propertiesof calcium phosphate (CaP) [7].…”
Section: Introductionmentioning
confidence: 99%